S239. EVALUATION OF A POINT OF CARE DEVICE IN IMPROVING PHYSICAL HEALTH CHECK UPTAKE IN TWO COMMUNITY MENTAL HEALTH TEAMS. (18th May 2020) - Butler, Joseph; de Cassan, Simone; Lennox, Belinda; Turner, Phillip; Glogowska, Margaret; Fanshawe, Tom; Hayward, Gail
Abstract: Background: Patients with Severe Mental Illness (SMI) have a life expectancy 15–20 years below that of the general population, mediated predominantly by the complications of poor cardiovascular health. Physical healthcare for this population is shared between General Practice (GP) and Community Mental Health Teams (CMHTs) and encompasses a NICE-recommended annual physical health check, to screen for cardiovascular complications. Audit findings in 2017 across the South of England show poor physical health check completion (38%), typically because HbA1c and Lipid Panel blood tests were omitted. Traditionally, patients are advised to attend their GP surgery for these tests, which can be a challenge for patients with SMI. There is a growing market of POC devices able to calculate an HbA1c or Lipid Panel in rapidly from 'fingerprick' samples of blood at, or near the site of the patient. The Cardiovascular Monitoring in Mental Health (CARMEN) project hypothesised that test uptake would be improved by implementation of a 'Point of Care' (POC) blood testing device in two CMHTs. Methods: We embedded the 'Afinion' device into an Early Intervention Team and an Adult Mental Health Team in Oxfordshire for six months. Training was provided to care coordinators with ongoing support to facilitate engagement with the device. We compared rates of blood test and full physical health check completion in the intervention teams to a matched early intervention team and adult mental health term in Buckinghamshire. We performed semi-structured interviews with patients receiving POC-augmented care and clinicians from the intervention teams. Results: Data showed that whilst the Adult Mental Health team did not engage with the device and saw no change in outcomes, the Early Intervention Team did engage and increased rates of physical health check completion from 22.6% to 40.3% of their caseload per 6 months. Completion in the control CMHT was 7.8%. Similar trends were seen in rates of HbA1c and Lipid Panel completion. Qualitative interviews revealed universal patient support for POC and diverse attitudes to the role of the mental health teams in providing physical healthcare. We explored how clinicians engaged and why they didn't engage with the device, and how access to POC modulated the therapeutic relationship. Discussion: Our findings show that using POC for Physical Health Checks is acceptable to patients with SMI and mental health care clinicians, many of whom are from a non-clinical background. In teams where it is well adopted, POC testing can improve physical health check completion in the SMI population, although our qualitative findings highlight important considerations for maximising clinician engagement.